How we treat endocrine complications of immune checkpoint inhibitors - Paschou, S.A. (ESMO Open, 2021)
Immune checkpoint inhibitors (ICIs) are antibodies that target certain immune checkpoints (ICs), such as cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), programmed death 1 (PD-1) or its ligand (PD-L1), and have emerged as a powerful new tool for oncologists. As these immune checkpoints are crucial for immunological self-tolerance, such therapies can trigger autoimmune adverse effects. Endocrine complications are among the most common, including hypophysitis, thyroid dysfunction, diabetes mellitus and primary adrenal insufficiency, while autoimmune polyendocrine syndrome type 2 (APS-2) may also present. The aim of this article is to critically appraise the literature and present (i) the biological role and function of the main ICs, (ii) the use of ICIs in the treatment of various cancer types, (iii) the endocrine complications of cancer immunotherapy with ICIs and (iv) practical recommendations for screening and management of patients with such endocrinopathies in everyday clinical practice.